(untitled) (Prosiding Konseling Kearifan Nusantara (KKN), 2024)
The most common mental health problem experienced by teenagers is anxiety. The increase in mental health problems among teenagers is very worrying. However, teenagers who most need mental health attention are reluctant to seek help, especially professional help. So this research aims to look at the picture of mental health in teenagers, the need to seek help, especially professional help, and apply the butterfly effect concept in everyday life to help overcome the mental health problems they experience. The method used in this research is a literature review in the form of an explanation of a theory, discovery and research obtained from reference materials such as books, scientific journals, articles and other documents. In this case, the researcher will first search various libraries to collect relevant information according to the topic. After obtaining various relevant library sources, the researcher then carries out analysis, comparing the results of one research with another and summarizing them. The results of this research are the high prevalence of mental health problems in teenagers, making teenagers need special attention and appropriate treatment in overcoming the mental health problems they experience. Therefore, the first step that can be taken is to seek professional help as an effort to resolve the mental problems they face. . However, another alternative that teenagers can do is to apply the butterfly effect concept in everyday life, such as saying thank you, improving good intentions, celebrating all achievements, creating positive habits, surrounding oneself with positive feelings and bringing changes to one’s well-being and the environment.